Evaluating the Effectiveness of Pubertal Preparedness Program in Terms of Knowledge and Attitude Regarding Pubertal Changes Among Pre-Adolescent Girls - Manisha Rani RN; Poonam Sheoran; Yogesh Kumar RN; Navjyot Singh (Tehran University of Medical Sciences, 2016)
Objective: To compare the knowledge and attitude regarding pubertal changes among pre - adolescent girls before and after the pubertal preparedness program (PPP) in experimental and comparison group. Materials and methods: A Quasi experimental (non- equivalent comparison group pretest posttest) design was adopted with 104pre-adolescentgirls (52 in each experimental and comparison group) of age 12-14years, selected by purposive sampling from two different Government schools of Ambala District. Knowledge and attitude was assessed using structured knowledge questionnaire (KR-20 = 0.74) and 5 point likert scale (Cronbach's alpha = 0.79) respectively. On the same day of pretest, PPP was administered and on 12th day FAQs reinforcement session was held only for experimental group. After 28 days, posttest was taken. Results: The computed t value of pretest of knowledge and attitude scores of pre-adolescent girls (1.97), (1.95) respectively in experimental and comparison group was found non-significant at 0.05 level of significance which shows that both group didn't differ significantly in their knowledge and attitude before the administration of intervention. Findings of unpaired 't' value of posttest knowledge and attitude scores of pre-adolescent girls (19.77), (17.17) respectively in experimental and comparison group were found significant at 0.05 level of significance, Thus knowledge and attitude of pre-adolescent girls were improved with PPP and FAQs session. Conclusion: Pubertal preparedness program and FAQs reinforcement session are effective in enhancing knowledge and developing favorable attitude among pre-adolescent girls.